Magnitude and durability of ProC6C-AlOH/Matrix-Mtm vaccine-induced malaria transmission-blocking antibodies in Burkinabe adults from a Phase 1 randomized trial - Mohammad Naghizadeh; Kazutoyo Miura; Ebenezer Addo Ofori; Carole Long; Issaka Sagara; Alfred B. Tiono; Jordan Plieskatt; Michael Theisen (Human Vaccines & Immunotherapeutics)
ProC6C is a multi-stage malaria vaccine designed to disrupt parasite transmission and prevent infection by incorporating three parasite proteins (Pfs230-Pro, Pfs48/45-6C, and CSP) in a single vaccine antigen. The Phase 1 clinical trial (PACTR202201848463189) conducted in Burkina Faso, showed ProC6C-AlOH/Matrix-M was safe, well tolerated, immunogenic and generated a functional antibody response to all three constituent antigens at the primary output (D70). As magnitude and durability are central to an efficacious malaria vaccine, analysis was expanded past the initial endpoint, to determine transmission-blocking antibodies (anti-Pfs230 and anti-Pfs48/45-6C) present through D180. Analysis of transmission-reducing activity (TRA) showed 7/20 samples remained biologically active at D180. To identify immune biomarkers for high levels of TRA, the Pfs48/45-6C IgG concentration (calculated relative to the transmission-blocking mAb TB31F) was compared among TRA positive and negative individuals. The magnitude of anti-Pfs48/45-6C IgG had an excellent predictive accuracy (area under the receiver operating curve [ROC AUC] >0.8) with a threshold of 8.7 μg/ml for significant TRA. Additionally, there was significant correlation of TRA and anti-Pfs48/45 epitope I IgG concentration but not significant correlation for anti-Pfs230-Pro IgG, suggesting that vaccine-induced anti-Pfs48/45-6C IgG is the main predictor of TRA. This finding was corroborated by the observation that complement had no effect on TRA in the standard membrane feeding assay (SMFA). Collectively, these efforts confirm the transmission-blocking attributes of ProC6C and suggest that an alternative dosing regimen be evaluated in future clinical trials to improve longevity of functional transmission-reducing antibodies.